2014
DOI: 10.4330/wjc.v6.i11.1218
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of moderate ischemic mitral valve regurgitation: Where do we stand?

Abstract: Ischemic mitral regurgitation (IMR) represents a common complication after myocardial infarction. The valve is anatomically normal and the incompetence is the result of papillary muscles displacement and annular dilatation, causing leaflets tethering. Functionally the leaflets present a restricted systolic motion due to tethering forces that displaces the coaptation surface toward the left ventricle apex. The patients present poor left ventricular function at the time of surgery and the severity of the mitral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Nevertheless, this procedure results in a recurrence rate of 20 to 30% after two to four years. [16,17] Recent studies have demonstrated the results in favor of the ring annuloplasty in terms of early survival compared to valve replacement; however, no differences were observed between mid-term results in ischemic MR. [18] On the other hand, there is a controversy on whether ring annuloplasty is superior to valve replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this procedure results in a recurrence rate of 20 to 30% after two to four years. [16,17] Recent studies have demonstrated the results in favor of the ring annuloplasty in terms of early survival compared to valve replacement; however, no differences were observed between mid-term results in ischemic MR. [18] On the other hand, there is a controversy on whether ring annuloplasty is superior to valve replacement.…”
Section: Discussionmentioning
confidence: 99%
“…IMR is an important complication of myocardial infarction and observed in 40% of patients with this condition. Regurgitation is caused by annular dilation and papillary muscle displacement in an anatomically normal valve [ 9 ] .…”
Section: Discussionmentioning
confidence: 99%
“…There is an agreement among clinicians that severe IMR should be surgically treated, however treatment of moderate IMR is still a matter of debate[ 10 ]. Many changes have occurred in surgical approaches over the past years.…”
Section: Choice Of Surgical Intervention In Severe Imr Repair mentioning
confidence: 99%